Biomarkers of oxidative stress, inflammation, and vascular dysfunction in inherited cystathionine β‐synthase deficient homocystinuria and the impact of taurine treatment in a phase 1/2 human clinical trial. Issue 3 (11th April 2019) - Van Hove, Johan L. K.; Freehauf, Cynthia L.; Ficicioglu, Can; Pena, Loren D. M.; Moreau, Kerrie L.; Henthorn, Thomas K.; Christians, Uwe; Jiang, Hua; Cowan, Tina M.; Young, Sarah P.; Hite, Michelle; Friederich, Marisa W.; et al.
Abstract: Study Objective: A phase 1/2 clinical trial was performed in individuals with cystathionine β synthase (CBS) deficient homocystinuria with aims to: (a) assess pharmacokinetics and safety of taurine therapy, (b) evaluate oxidative stress, inflammation, and vascular function in CBS deficiency, and (c) evaluate the impact of short‐term taurine treatment. Methods: Individuals with pyridoxine‐nonresponsive CBS deficiency with homocysteine >50 μM, without inflammatory disorder or on antioxidant therapy were enrolled. Biomarkers of oxidative stress and inflammation, endothelial function (brachial artery flow‐mediated dilation [FMD]), and disease‐related metabolites obtained at baseline were compared to normal values. While maintaining current treatment, patients were treated with 75 mg/kg taurine twice daily, and treatment response assessed after 4 hours and 4 days. Results: Fourteen patients (8‐35 years; 8 males, 6 females) were enrolled with baseline homocysteine levels 161 ± 67 μM. The study found high‐dose taurine to be safe when excluding preexisting hypertriglyceridemia. Taurine pharmacokinetics showed a rapid peak level returning to near normal levels at 12 hours, but had slow accumulation and elevated predosing levels after 4 days of treatment. Only a single parameter of oxidative stress, 2, 3‐dinor‐8‐isoprostaglandin‐F2α, was elevated at baseline, with no elevated inflammatory parameters, and no change in FMD values overall. Taurine had no effect on any of these parameters. However, the effect of taurine was strongly related to pretreatment FMD values; and taurine significantly improved FMD in the subset of individuals with pretreatment FMD values <10% and in individuals with homocysteine levels >125 μM, pertinent to endothelial function. Conclusion: Taurine improves endothelial function in CBS‐deficient homocystinuria in patients with preexisting reduced function.